Strategi UPT Bahasa IAIN Parepare dalam Meningkatkan Skill Berbahasa Inggris Mahasiswa IAIN Parepare - T, Tenriyati (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
This study aims to describe the UPT Language IAIN Parepare strategy in Improving the Language Skills of IAIN Parepare Students. This research is more focused on the author's two main goals in this article, namely: What strategies are used by UPT Language IAIN Parepare in improving the language skills of IAIN Parepare students and how UPT Language students guide and provide training. The type of approach in this research is qualitative research using data triangulation and the objects in this study are IAIN Parepare students who are directly involved in the Language UPT IAIN Parepare. Then the subject of this research is a UPT Language Strategy for IAIN Parepare and IAIN Parepare Students. Furthermore, data collection techniques in this study are observation, interview, and documentation techniques. The tools used in collecting data are interview guides and documentation. This type of data processing is done using a qualitative descriptive analysis. The results of this research show that there are 5 UPT Language strategies for IAIN Parepare in improving the language skills of IAIN Parepare students and presenting tutors who are masters who are already experts in the language.